The Analysis of Mathematical Critical Thinking Ability and Mathematical Creativity: Judging from the Process of Deriving the Fermi-Dirac Formula - Nehru, Nehru; Ananda, Rizki; Zb, Aminah; Navalyyan, Devie (International Journal of Education and Teaching Zone, 2022)
This study aims to see and simultaneously describe the ability to think critically and creatively in student physics teacher candidates in the Fermi-Dirac course. Descriptive quantitative was used as the method of this research. Data collection in the study used tests on the cognitive domain in the form of a description of 8 questions where four measured critical thinking skills and four questions measured creative thinking skills. The data analysis process was carried out qualitatively and then described to determine the students' mathematical critical thinking and creative thinking skills, which were then assessed in distribution based on the categories that had been created. The data and facts that the researchers found after the study showed that the average mathematical thinking ability of students was in the Good Enough category, and the average mathematical communication ability of students were also in the Good Enough category.